Multiplet Mass Spectra of the SU(3) Skyrme Model with Color Symmetry Breaking and the Guadagnini terms - Irwandi Irwandi; Triyanta Triyanta (Indonesian Journal of Physics, 2006)
We consider an SU(3) Skyrme model, defined by embedding the SU(2) hedgehog ansatz and adding with a color symmetry breaking and the Guadagnini terms. The ground state energy of the SU(3) Skyrme model is equal to that of the SU(2) Skyrme model. In contrast to the dynamic energy of the SU(2) Skyrme model which is associated to only three rotational axes, the dynamic energy of the SU(3) Skyrme model is associated with eight rotational axes. Quantization of the spatial axis components of the angular momenta follows the ordinary quantum quantization of angular momenta, while quantization for the collective axis components and for the eight axis component follow, respectively, the quadratic Casimir operator and the Wess-Zumino term. The color symmetry breaking and the Guadagnini terms are added in the model in order to obtain more splitting mass spectra, mass spectra that are sensitive to the isospin and hypercharge quantum numbers. In this paper, we calculate the octet, decuplet, and anti decuplet mass spectra using certain values of parameters. The results for the octet and decuplet are between 1% to 3% mass discrepancies compared to the experimental values. We do not compare the antidecuplet results to the experiment, as the experimental masses are not well established.